1996
DOI: 10.1111/j.1439-0523.1996.tb00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection response for carbon isotope discrimination in a Triticum polonicum×T. durum cross: Potential interest for improvement of water efficiency in durum wheat

Abstract: This study has been conducted to evaluate the usefulness of carbon isotope discrimination (A) in mature kernels as a criterion for the improvement of water-use efficiency and yield under drought in durum wheat. For this purpose, Triticum durum 'Om Rabi 5' was crossed with T. polonicum pseudochrysospermum 9 (Tp9) which has been found to be more drought tolerant and to have a lower carbon isotope discrimination value of the grain. The Fj population showed a wide segregation for carbon isotope discrimination. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…The significant negative associations between Δ and days to heading and days to anthesis observed in the present study, particularly under rainfed conditions, have also been reported by Al Hakimi et al. (1996).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The significant negative associations between Δ and days to heading and days to anthesis observed in the present study, particularly under rainfed conditions, have also been reported by Al Hakimi et al. (1996).…”
Section: Discussionsupporting
confidence: 87%
“…Patterns in the relationship between grain yield and Δ can also be masked by phenological differences among genotypes that may affect yield and Δ. Under Mediterranean conditions for example, early genotypes generally show higher Δ values (Al Hakimi et al. 1996, Araus et al.…”
Section: Introductionmentioning
confidence: 99%
“…Einkorn wheat, (Triticum monococcum subsp. monococcum) was found previously to have a similar (Austin et al 1986) or even higher (Al Hakimi et al 1996) biomass, compared to bread wheat. Variation in grain yield was much more driven by differences in harvest index (r = 0.873***) than by differences in biomass production (r = 0.661**).…”
Section: Discussionmentioning
confidence: 74%
“…2001c). Moreover, high broad‐sense heritability values were reported for ΔG in several cereal species including durum wheat (Condon and Richards 1992, Al Hakimi et al. 1996, Merah et al.…”
Section: Discussionmentioning
confidence: 99%